ANALISIS KESELAMATAN LALU-LINTAS JL.SOEKARNO HATTA BALIKPAPAN - Maslina Maslina; Bima Dhevrando (Universitas Lambung Mangkurat, 2019)
Soekarno Hatta Road is one of the road shaft beetween Balikpapan and Samarinda which has 119 kilometres long. This road is province roads that had been through out or passed by with typical heavy and light vehicles which has high intensity accident level. This research is aimed to devise factor and characteristic of accidents along Sokearno Hatta roads from zero kilometres until 13th kilometres. This research begun with roads survey observation and secondary data collection including with roads accidents documents for the pass 3 years.( which is in years of 2015 – 2017). Data analysis prepared with calculating numbers of accidents using formula EAN (Equivalent Accidents Number) and UCL Method (Upper Control Limit) for determination area with high risk accidents (Black Spot). Anatomy Accidents Data Documents were enumerated to analyze in that specified area. That can be conclude that the numbers of accidents on Soekarno Hatta Street from zero kilometres until 13th kilometreswith EAN method i.g : more than 84 times bigger different from UCL value i.g: 43,3. Accidents that was happened in the mornings at weekdays Monday to Friday which were implicate 2 motorcycles and passenger in fifthteen till twenty years old students (boys).